Graph 6y+3=-18x

Math
6y+3=-18x
Solve for y.
Tap for more steps…
Subtract 3 from both sides of the equation.
6y=-18x-3
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6y=-18x-3 by 6.
6y6=-18×6+-36
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6y6=-18×6+-36
Divide y by 1.
y=-18×6+-36
y=-18×6+-36
Simplify each term.
Tap for more steps…
Cancel the common factor of -18 and 6.
Tap for more steps…
Factor 6 out of -18x.
y=6(-3x)6+-36
Cancel the common factors.
Tap for more steps…
Factor 6 out of 6.
y=6(-3x)6(1)+-36
Cancel the common factor.
y=6(-3x)6⋅1+-36
Rewrite the expression.
y=-3×1+-36
Divide -3x by 1.
y=-3x+-36
y=-3x+-36
y=-3x+-36
Cancel the common factor of -3 and 6.
Tap for more steps…
Factor 3 out of -3.
y=-3x+3(-1)6
Cancel the common factors.
Tap for more steps…
Factor 3 out of 6.
y=-3x+3⋅-13⋅2
Cancel the common factor.
y=-3x+3⋅-13⋅2
Rewrite the expression.
y=-3x+-12
y=-3x+-12
y=-3x+-12
Move the negative in front of the fraction.
y=-3x-12
y=-3x-12
y=-3x-12
y=-3x-12
Use the slope-intercept form to find the slope and y-intercept.
Tap for more steps…
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Find the values of m and b using the form y=mx+b.
m=-3
b=-12
The slope of the line is the value of m, and the y-intercept is the value of b.
Slope: -3
y-intercept: -12
Slope: -3
y-intercept: -12
Any line can be graphed using two points. Select two x values, and plug them into the equation to find the corresponding y values.
Tap for more steps…
Choose 0 to substitute in for x to find the ordered pair.
Tap for more steps…
Replace the variable x with 0 in the expression.
f(0)=-3⋅0-12
Simplify the result.
Tap for more steps…
Multiply -3 by 0.
f(0)=0-12
Subtract 12 from 0.
f(0)=-12
The final answer is -12.
-12
-12
The y value at x=0 is -12.
y=-12
y=-12
Choose 1 to substitute in for x to find the ordered pair.
Tap for more steps…
Replace the variable x with 1 in the expression.
f(1)=-3⋅1-12
Simplify the result.
Tap for more steps…
Multiply -3 by 1.
f(1)=-3-12
To write -3 as a fraction with a common denominator, multiply by 22.
f(1)=-3⋅22-12
Combine -3 and 22.
f(1)=-3⋅22-12
Combine the numerators over the common denominator.
f(1)=-3⋅2-12
Simplify the numerator.
Tap for more steps…
Multiply -3 by 2.
f(1)=-6-12
Subtract 1 from -6.
f(1)=-72
f(1)=-72
Move the negative in front of the fraction.
f(1)=-72
The final answer is -72.
-72
-72
The y value at x=1 is -72.
y=-72
y=-72
Create a table of the x and y values.
xy0-121-72
xy0-121-72
Graph the line using the slope and the y-intercept, or the points.
Slope: -3
y-intercept: -12
xy0-121-72
Graph 6y+3=-18x

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top